Suplemento al Tesoro de la lengua española castellana - Covarrubias Orozco, Sebastián de, 1539-1613 (Ediciones Polifemo, 2001)
This work is a transcription of the manuscript written by S. Covarrubias, found as the Ms. 6159 of the Biblioteca Nacional de Madrid. The manuscript covers from the word Abacuq to the word Moises. The rest of the work has not been found.